Isolation and characterization of pathogenic Vibrio on tiger grouper Epinephelus fuscoguttatus - Ilmiah, .; Sukenda, .; Widanarni, .; Harris, Enang (Jurnal Akuakultur Indonesia, 2012)
This study was aimed to obtain pathogenic bacterial isolate causing vibriosis disease. Isolation of Vibrio was conducted from maribound tiger grouper collected from floating net cage in Barru Regency using TCBS medium. Ability to cause vibriosis was confirmed by pathogenicity test performed by mean injecting the tiger grouper juveniles with bacterial suspension at concentration of 106 CFU/fish and mortality of fish during seven days observation then was noted. Then, the Vibrio pathogenic isolate was characterized and identified based on morphology, growth, and biochemical features. Moreover, the most pathogenic isolate was identified by molecular analysis of 16S-rRNA gene sequences. The results showed that three potential isolates caused Vibriosis disease in tiger grouper culture. The isolates tested were biochemically identified as Vibrio metschnikovii, V. parahaemolyticus, and V. mimicus. The most virulent among isolates was V. parahaemolyticus. Keywords: isolation, characterization, pathogenic, vibriosis, tiger grouper